Simulation of Grid Connected Solar Power System and Harmonic Reduction - Subhash Sharma; Dr Anju Gupta; Uma Yadav; Dr DK Bhalla (Journal of Power Electronics and Devices, 2018)
The use alternative sources of Power Generation is the need of today. In general, the renewable energy resources are pollution free (Such as Wind, Hydro, Solar), easily constructible, and require less maintenance as compared to conventional energy sources (Such as Natural gas and oil). Most effective method for generation of Power, among renewable energy sources, is photovoltaic system (using solar cell). Solar Photovoltaic System is easy to install, clean and light. Once installed, it has no recurring expenditure except the battery. This Paper deals with connecting solar system with 3 phase grid system. Thereby reducing the need of battery. MPPT technique is used to extract the maximum power obtained from the sun radiation and transfer it to grid. Three phase inverter is also used to convert DC, of boost converter, into AC, which is fed into grid. Further, harmonic is also reduced from the grid by using filters.